(untitled) (Altre Modernità, 2014)
These are the signs that mark Margarita Mateo Palmer’s novel. This writing from the asylum challenges the preludes to immobility evoked by a place of order and restraint, thus enabling the emergence of a series of paths, which manage to shake the broken identity of the protagonist, Gelsomina, and of her time. Those intersections allow reflection on the contemporary Cuban condition, bent by the twilight of the revolutionary ideals, and at the same time to wonder about the human condition, savaged by the centripetal drive of consumerism and disposable worldviews, which are increasingly prone to wipe out any desiring tension in favour of magical objects of pleasure, hollow and ephemeral pret a porter [1] simulacra. This paper aims to analyse the narrative structure of the novel by means of the tools offered by Massimo Recalcati’s interpretation of Lacan’s psychoanalysis. Particular attention will be devoted to the interplay between the protagonists, who embody clinical figures and also symbolise different dimensions of contemporary Cuban experience. [1] This reading of the twilight of ideologies and of the vaporization of the Name of the Father is indebted to Massimo Recalcati’s thought (2010; 2011).